Bio‐inspired Domino oxa‐Michael/Diels–Alder/oxa‐Michael Dimerization of para‐Quinols. (25th April 2018) - Green, Nicholas J.; Connolly, Catherine A.; Rietdijk, Koen P. W.; Nichol, Gary S.; Duarte, Fernanda; Lawrence, Andrew L.
Abstract: A bio‐inspired, pyrrolidine‐mediated, dimerization of para ‐quinols has been developed. It represents one of the most complex, yet general, dimerization reactions ever disclosed, selectively forming four new bonds, four new rings, and eight new contiguous stereogenic centres. The para ‐quinol starting materials are easily handled, bench‐stable compounds, accessed in just one step from aromatic feedstocks. The reaction can be scaled up to give grams of polycyclic material, primed for further elaboration. Abstract : Eine für alle : Eine biologisch inspirierte, hoch komplexe, aber allgemeingültige Dimerisierung von para ‐Chinolen liefert selektiv vier neue Bindungen, vier neue Ringe und acht neue, benachbarte Stereozentren. Die para ‐Chinole sind leicht handhabbar und stabil und in einer Stufe aus aromatischen Edukten zugänglich. Die Reaktion ist im Gramm‐Maßstab durchführbar und liefert polycyclisches Material, das bereit für die weitere Umsetzung ist.